Anime characters creation using generative adversarial networks with user inputs - Ang, Himari Lixin (Nanyang Technological University, 2024)
Generative Adversarial Network (GAN) is a framework that has been used to generate realistic images of faces, objects, and even landscapes. With its increasing popularity, it can be used to generate anime facial images. Diffusion models have also recently been on the rise with models like Stable Diffusion taking the center stage due to how realistic the images generated are. These models has potential applications in the entertainment industry for creating virtual worlds.